PENGARUH PENCUCIAN DAN PUPUK KANDANG TERHADAP PRODUKSI PADI SAWAH DI PROVINSI NAD - Chairunas Chairunas (Jurnal Floratek, 2006)
Effect of Leaching and Manure on Production of Wet Field Rice Chairunas Balai Pengkajian Teknologi Pertanian (BPTP) Nanggroe Aceh Darussalam  ABSTRACT The research objective was to get the appropriate technological packet of lowland rice cultivation on tsunami-affected land to increase land productivity. The research was conducted in Bireuen District of Aceh Province. Result of salinity measurement using Electro Magnetic (EM-38) tool on tsunami-affected land showed that soil salinity has decreased (ECa = 0,5 dS/m ~ Ece = 0,52 dS/m) but it was still higher than that of unaffected land.  Soil analyses showed that organic content was very low (0.97 %) and potassium was also low (0.52).  In contrast, there were very high contents of Mg (8.58 cmol/kg) and Ca (7.00 cmol/kg).  In dry season of cropping year 2005 (April-September), farmers harvested rice as much as 30-50 % of normal productivity (2.5 – 4 tons/ha).  Effort in increasing land productivity needs introduction of technological packet such as manure combined with potassium application.  In this research, manure used was from processed chicken waste in dosage of 0 and 2 tons/hectare combined with KCl fertilizer as source of potassium in dosage of 50 tons/ha and 75 tons/ha.  Basic fertilizer used were 200 kgs/ha urea and 100 kgs/ha SP36.  The research applied factorial Randomized Block Design, consisted of 8 application combinations and 3 replications.  The result showed that application of 2 tons/ha manure combined with 75 kgs/ha KCl, 200 kgs/ha urea and 100 kgs/ha SP36 and two times of leaching gave the highest rice yield (11,54 tons/ha).  The lowest yield of 8.30 tons/ha (30 % higher than average farmer yield before tsunami) was found on farmer’s application (without leaching, no manure, 200 kgs/ha urea, 100 kgs/ha Sp36 and 50 kgs/ha KCl).